The center of a circle whose equation is x^2 +y^2 – 12x – 2y +12 = 0 is (6,1)
<h3>Equation of a circle</h3>
The standard equation of a circle is expressed as:
x^2 + y^2 + 2gx + 2fy + c = 0
where:
(-g, -f) is the centre of the circle
Given the equations
x^2 +y^2 – 12x – 2y +12 = 0
Compare
2gx = -12x
g = -6
Simiarly
-2y = 2fy
f = -1
Centre = (6, 1)
Hence the center of a circle whose equation is x^2 +y^2 – 12x – 2y +12 = 0 is (6,1)
Learn more on equation of a circle here: brainly.com/question/1506955
37+n=p because all your doing is putting the numbers into a problem with the correct signs.
If you want to multiply (2*x + 5) and (2*x - 5), you can do this using the following steps:
(2*x + 5) * (2*x - 5) = 4*x^2 - 10*x + 10*x - 25 = 4*x^2 - 25
The correct result is 4*x^2 - 25.
(300 box/h) * (0.8 cup/box) * (1 gal)/(16 cup) = 300*0.8/16 gal/h
.. = 15 gal/h
Jim's factory needs 15 gallons of juice per hour.
Answer:15
Step-by-step explanation: